Category change and incidence of malignancy in Bosniak category II, IIF and III lesions at King Chulalongkorn Memorial Hospital (KCMH) - Sriyook, Aniwat; Sasiwimonphan, Kewalee (Chulalongkorn Medical Journal, 2023)
Background : The widely-used classification for renal cysts is Bosniak classification which is also accepted by urologists for diagnoses and management approaches to cystic renal masses. The recent studies show variable incidences of malignancy in Bosniak category II, IIF and III lesions. Even in Bosniak category II lesion which was previously believed to be benign which had no need to follow-up has incidence of malignancy. Objective : To detect the incidence of malignancy, time and rates of progression in complexity of Bosniak category II, IIF and III lesions at King Chulalongkorn Memorial Hospital (KCMH). Methods : Searched the term “complex renal cyst”, “Bosniak”, “hemorrhagic cyst” and “complicated cyst” in computed tomographic (CT) and magnetic resonance imaging (MRI) studies from pictures archiving and communications system (PACS) of our institution from January 1, 2011, to December 31, 2011. Patients who had Bosniak category II, IIF and III lesions and radiological follow-up including CT, MRI and ultrasonography more than 2 years were included in this study. Re-classification of the cysts was independently performed by two blinded readers. Recorded data was sex, age, history or coexisting neoplasm, the number of cysts, characteristic of cysts, duration of follow-up, number of progression in complexity, time to progression and rate of malignancy. A total of 109 cases with161 cysts were yielded. Results : A total of 161 cysts were initially reclassified to 144 Bosniak II lesions, 15 Bosniak IIF lesions and 2 Bosniak III lesions. Good agreement of classification of Bosniak category of these cysts is noted between two readers with difference experience. One lesion (6.7%) of resected Bosniak IIF was malignant. Four lesions (2.8%) in Bosniak II had progression in complexity; three lesions were reclassified as Bosniak IIF with time to progression of 1,626, 1,423 and 477 days and one lesion reclassified as Bosniak III with time to progression of 1,904 days. Conclusion : The malignancy rates of Bosniak II, IIF and III lesions in our study are 0%, 6.7% and 0%, respectively. This may be underestimated as compared with those of prior studies due to small sample size.However, imaging surveillance of Bosniak IIF lesion is stilling recommend due to the chance of malignancy and progression of complexity in a group of Bosniak II lesion which has more case numbers.